Fermentation endpoint detection of Soybean using specially designed Pd-coated FBG stress sensor - Mirza, Jawad; Atieh, Ahmad; Kanwal, Benish; Kanwal, Firdos; Aziz, Imran; Almogren, Ahmad (Frontiers in Physics, 2025)
Determining the fermentation endpoint of organic compounds is critical for optimizing yield, ensuring the product consistency, and minimizing byproducts. However, conventional detection methods are slow, labor-intensive, and lack real-time monitoring, limiting their suitability for industrial automation. We propose a novel, non-destructive method for real-time detection of fermentation endpoint of Soybean using Palladium (Pd)-coated fiber Bragg grating (FBG) stress sensor. The fermentation endpoint can be detected by monitoring the shift in Bragg wavelength caused by the stress in Pd-coated FBG sensor due to the volume expansion of the Pd coating upon the formation of Palladium Hydride (PdHx) after Hydrogen (H2) gas absorption, which is released as a byproduct during Soybean fermentation. The Pd-coated FBG stress sensor is analytically designed and validated using OptiSystem simulation tool, achieving a high sensitivity of 61.6 p.m./MPa. Our findings confirm that this method provides a simple, efficient, and real-time solution for monitoring the fermentation process of organic compounds that produce H2 offering significant advantages over traditional techniques.